The Embodiment of Contempt: Ontario Provincial Prison Food. (April 2023) - Struthers Montford, Kelly
Prison food is central to the prison experience and is a physically invasive manifestation of carceral power. This article draws on 61 interviews with individuals with lived experience of provincial prisons in Ontario, Canada. Participants reported that the food was unhealthy, small-portioned, bland, and steamed to the point that they could not discern what they were eating. Others reported living in fear of the food, whether because it was molding, spoiled, or had been tampered with. For many participants, their experience of incarceration was that of hunger and unwanted bodily changes. Poor quality prison food bolstered an underground food economy in which trading, gambling, or intimidation were used by prisoners to access more and/or better foods. Overall, prison food was a means through which social, political, and institutional contempt for prisoners was communicated to and embodied by prisoners.